THE USE OF WASTEWATER SLUDGE FROM A CASSAVA STARCH PLANT AS BRICK MATERIAL - Srivichai, Piyavadee; Thongtip, Sakesun (Srinakharinwirot University Journal of Sciences and Technology, 2021)
The aim of this research was to determine the optimum mixing ratio of UASB (Up-flow anaerobic sludge blanket, UASB) sludge from a modified cassava starch plant as a material in the fried clay brick production. The amounts of hazardous chemicals were initial studied that their level were lower than The Total Threshold Limit Concentration (TTLC) (The Notification of The Ministry of Industry on Disposal of Wastes or Unusable Materials B.E. 2548 (2005). Therefore, the UASB sludge is not hazardous waste that it can be used as material to produce brick. And it was found that at the sludge content of 10% by dry weight basis were appropriate. It had the low water adsorption rate and high compressive strength at 22.6±1.5% and 9.6±1.6 MPa, respectively, which according to Thailand Industrial Standard (TIS 77 -2545). When the increase in the percentage of sludge added, that resulted in the decreased strength of the produced brick with the higher water adsorption rates and the less compressive strength. The results indicated that the UASB sludge was suitable to use as a material in the brick production. Moreover, it is a method to adding value of sludge and reducing the environmental impacts from ineffective disposal management.